Putzger historischer Weltatlas - Brückner, Ernst; Putzger, F. W. (Friedrich Wilhelm), 1849-1913 (Berlin : Cornelsen Verlag, 2001)
Vor- und Frühgeschichte - Altertum - Mittelalter - Neuzeit - 19 - und 20 - Jahrhundert